One-Step Preparation of Phenyl Boron-Modified Magnetic Mesoporous Silica for Selective Enrichment of cis-Diol-Containing Substances - Hua Fu; Jing Hu; Min Zhang; Yuerong Wang; Hongyang Zhang; Ping Hu (Molecules, 2018)
For enrichment and separation of cis-diol-containing compounds from biomatrix, a new type of magnetic nanoparticles named MS-48-PBSC, whichwas facilely prepared in a one-step heterogeneous reaction. The morphology results demonstrated that the MS-48-PBSC was a spherical nanomaterial containing a core of silica-coated magnetic particle with a diameter of about 200 nm, and a cover layer of mesoporous silica with a thickness of approximate 50 nm. The characterization results showed that MS-48-PBSC presented a pore size of 4.2 nm, a surface area of 548 m2·g−1, and a pore volume of 0.30 cm3·g−1. The MS-48-PBSC also exhibited magnetism of 42 emu·g−1 that contributed to the easy separation of magnetic nanomaterial within 30 s from the matrix with the aid of the external magnetic field. In addition, the MS-48-PBSC exhibited high adsorption capacity for adenosine, xanthosine, uridine, sialic acid, and teicoplanin with 0.60, 0.51, 0.42, 0.75, and 1.26 mg/g, respectively, and showed a high selectivity for the cis-diol structure compounds, relative to interferences of bovine serum albumin, guanine, uric acid, and xanthine. The recoveries of adenosine, xanthosine, uridine, sialic acid, and teicoplanin were 71.8–114.1% with relative standard deviation (RSD) ≤ 8.6%, and the enrichment factors of them were 8–11. MS-48-PBSC exhibited quick separation capability from matrix, high adsorption capacity and size exclusion for bovine serum albumin, which could meet the requirements of separation and enrichment for substances with a cis-diol structure.